Analisis Metode Pembelajaran Bahasa Arab di Sekolah: Kajian Teoretis dan Implikasinya dalam Konteks Pendidikan Modern - Triani Triani (Sanaamul Quran: Jurnal Wawasan Keislaman, 2025)
This study aims to analyze various Arabic language teaching methods used in educational institutions in Indonesia and to identify the strengths and weaknesses of each method. The research employs a descriptive qualitative approach using a literature review method. The findings indicate that there is no single ideal method suitable for all contexts, and a combination of grammar-translation, communicative, and reading-writing (qira’ah-kitabah) methods is considered the most realistic to implement at the elementary and secondary levels. The study also emphasizes the importance of integrating technology into Arabic language learning, such as the use of digital media and Learning Management Systems (LMS), to enhance students’ motivation and learning quality. The results of this research are expected to serve as a reference for developing more effective and adaptive Arabic language curricula and teaching methods in Indonesia that meet the needs of students in the digital era.